Evaluation of chronic kidney disease in cancer patients: is there a preferred estimation formula?. Issue 11 (1st November 2018) - Sleilalty, Ghassan; El Rassy, Elie; Assi, Tarek; Al Rassy, Nathalie; Nasseh, Jessica; Rizkallah, Jamale; Finianos, Serge; Azar, Hiba; Chelala, Dania N.; El Karak, Fadi; Kattan, Joseph; Ghosn, Marwan
Abstract: Background: The evaluation of chronic kidney disease (CKD) in cancer patients seems to rely mostly on the Cockcroft‐Gault (CG) formula or the creatinine levels to adjust treatment dosages which is a practice refuted by internists. Aims: We evaluate the overall agreement of the CG, modification of diet in renal disease (MDRD) and CKD–epidemiology collaboration equations (CKD‐EPI) equation with the newly devised Janowitz and Williams' (JW) equation. Methods: The renal function was estimated in 235 cancer patients according to the CG, MDRD, body surface area (BSA)‐adjusted MDRD, CKD‐EPI, BSA‐adjusted CKD‐EPI and JW formulae. Results: JW equation was more in agreement with CG and CKD‐EPI estimations than the other equations. Taking JW equation as reference, receiver operating characteristic curve analysis showed that CG eGFR had the higher area under the curve when compared with other equations. Hierarchical cluster analysis showed more proximity between CG and JW equations than the other equations. Conclusion: The newly proposed JW eGFR estimation was more in agreement with CG equation than the other equations.